Teachers Perceptions towards Social Media Use to Improve Professional Development and Integration in English Language Teaching - Agustrianita Agustrianita (Universitas Muhammadiyah Semarang, 2017)
Social media such as Facebook, BBM, Whatsapp, Instagram, Youtube, Twitter, E-mail, LinkedIn, Edmodo, Blog, and Skype have significant impact on aspect of life, including English education. Teachers need to know not only social media use as a tool to enhance professional development,but also integrate social media in English Language Teaching (ELT) because the students who are Digital Natives are already familiar with social media and they feel quite comfortable with each innovation and changes. This study aims at investigating the teachers professional development as well as their perspectives towardimplementing the social media into EFL teaching and learning. It is formulated in order to answer two research questions: (1) What is the teachersperceptionstoward the implementing of social media in developing their professional inELT? (2) How do the teachers integrate social media in ELT? Data of this qualitative study were taken from survey through questionnaire which was administered to 20 participants. The findings of this research show the participants havepositive perspectives about the implementation social media as a helpful learning tool to develop their professional. Moreover, social media can beapplied with a variety of advantages in ELT. The recommendation is that the EFL teachers is worth trying to find the available social media for their professional development and implement social media to create more effective teaching and learning activities.